Adicción a Internet como factor asociado a depresión en estudiantes de medicina - Cruzado Landauro, Jherson Jesús (2023)
To determine if Internet addiction is associated with depression in students of the School of Medicine of the National University of Trujillo. MATERIAL AND METHOD: An analytical and cross-sectional study was carried out where 578 students from the first to sixth year of the School of Medicine of the National University of Trujillo were surveyed during the year 2022, using the Young test and the Zung scale, to to evaluate Internet addiction and depression respectively. The Chi-square test was applied to determine the association between both variables. (CI:95%) RESULTS: The prevalence of Internet addiction in medical students was 34.1%, while the prevalence of depression was 54.2%. (Pearson's X2: 30.426, p=0.0000). The average daily use of Internet hours academically and recreationally was 4.59 and 7.15 hours, respectively. The device with which they connected to the internet the longest was the cell phone, followed by laptop and tablet. CONCLUSION: Internet addiction is significantly associated with depression in medical students at the National University of Trujillo.